2020
DOI: 10.3389/fpsyg.2020.01795
|View full text |Cite
|
Sign up to set email alerts
|

Are There Multiple Motivators for Helping Behavior in Rats?

Abstract: Empathy is the ability to (a) be affected by and share the emotional state of another; (b) assess the reasons for the other’s state; and (c) identify with the other, adopting their perspective. This phenomenon has been shown to exist in several species and is proposed as a motivator for prosocial behavior. The experimental study of this feature in laboratory rodents is a more viable alternative in comparison to wild animals. A recent report showed that rats opened a door to free their cage mate from a restrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…In rats, the opening latency decreased across trials, indicating a learning curve 37 . Social facilitation learning is another alternative explanation in which the presence of conspecifics could have influenced the behaviour in others 37 . For example, the rescue behaviour of the female could have been triggered or facilitated by the presence of other boars as well as influenced to be more efficient or fast.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In rats, the opening latency decreased across trials, indicating a learning curve 37 . Social facilitation learning is another alternative explanation in which the presence of conspecifics could have influenced the behaviour in others 37 . For example, the rescue behaviour of the female could have been triggered or facilitated by the presence of other boars as well as influenced to be more efficient or fast.…”
Section: Discussionmentioning
confidence: 95%
“…Prosocial behaviour, however, does not have to be motivated only by empathy 8 . Other alternative underlying mechanisms, such as social contact seeking 14 , a selfish act to terminate the signals of stress 8,65 , curiosity 37 , and an opening of the trap by accident, have been proposed. We can, however, rule out most of these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the authors claimed that their study showed the irrelevance of social rewards for rescue occurrence. These results were then followed by another study [ 87 ]. Perhaps most importantly, the authors showed that rats that previously rescued their cagemates from the restrainers showed no decrease in the frequency of opening or the time to open the restrainers when they were then presented to them empty.…”
Section: Rescue Behavior In Other Taxamentioning
confidence: 99%